Antagonistic effect of toll-like receptor signaling and bacterial infections on transplantation tolerance - Alegre, Maria-Luisa (2009)
The induction of donor-specific tolerance remains a major goal in the field of transplantation immunology. Therapies that target costimulatory molecules can induce tolerance to heart and pancreatic islet allografts in mouse models, but fail to do so following transplantation of skin or intestinal allografts. We have proposed that organs colonized by commensal bacteria such as skin, lung and intestine may be resistant to such therapies as a result of bacterial translocation at the time of transplantation, which may promote antigen-presenting cell (APC) maturation and the production of pro-inflammatory cytokines, consequently enhancing responses of alloreactive T cells. Our results indicate that the inability to sense signaling by most toll-like receptors (TLRs), as well as by interleukin (IL)-1R and IL-18R, as a result of genetic ablation of myeloid differentiation factor 88 (MyD88) promotes the acceptance of skin allografts. Conversely, TLR signals and infections by a model bacterium, Listeria monocytogenes (LM), at the time of transplantation can prevent the induction of transplantation tolerance. The effects of the TLR9 agonist CpG are MyD88-dependent, while the pro-rejection capacity of LM depends on the intracellular sensing of LM and the production of type I interferon (IFN). Therefore, transiently targeting these innate, pro-inflammatory pathways may have therapeutic value to promote transplantation tolerance.